The intersection of tradition and economy: Exploring the sacrificial practices in Zanzibar’s Blue Economy - Issa G. Ahmed; Bakar Khatib Faki (Journal of Economics and Business Letters, 2026)
The blue economy is now emerging as the essential conceptual framework to know how communities living on the coasts cope with sustainability and identify issues and build marine-based livelihoods. This paper aims to discuss the intersection between tradition and economy by investigating the issues of sacrifice in the Zanzibar fishing industry. That of the research, which relies on the accounts of fishermen and field observations in addition to questionnaire (n=22) results, concludes that whereas some individuals consider ritual sacrifices to be symbolic to more ceremonial rituals required to reach prosperous catches and economic prosperity, other people perceive it to be expensive or even destructive. These practices show how the cultural rituals and belief systems inform the way resources are utilized, how they make their revenue, and the way communities are built. They also highlight the relevant concerns of the correlation between traditional worldviews and the existing policies that facilitate the development of the blue economy. By placing sacrificial activity in the larger context of the fisheries livelihoods and cultural sustainability debate, this article highlights the need to incorporate socio-cultural considerations into strategies to support inclusive and resilient blue economies particularly where local systems of belief continue to have an impact.